Pengaruh Manajemen Keuangan Terhadap Kinerja Perusahaan: Studi Pada Sektor Perbankan - Muhammad Efendy; M Ammar Fikri H; Agus Wahyudi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of financial management on company performance in the banking sector. The main variables analyzed include the decision to invest, the decision on funding, and the dividend policy as independent variables, while financial performance is measured using Return on Assets (ROA) as an independent variable. The data used are from the results of the annual financial reports of companies in banking listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The results of this study indicate that investment decisions and dividend policies have a significant positive effect on the company's financial performance, while funding decisions do not have a significant effect. This study conducts an in-depth analysis of the influence of leverage, profitability and company size on earnings management in 10 banking companies on the Indonesia Stock Exchange for the period 2011-2013. The results of the study show that only company size has a significant negative effect on earnings management, while leverage and profitability do not have a significant effect. This study concludes that large companies have better financial management capabilities, so they tend to do less earnings management.